2018
DOI: 10.1016/j.bja.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Propofol-induced unresponsiveness is associated with impaired feedforward connectivity in cortical hierarchy

Abstract: Background: Impaired consciousness has been associated with impaired cortical signal propagation after transcranial magnetic stimulation (TMS). We hypothesised that the reduced current propagation under propofol-induced unresponsiveness is associated with changes in both feedforward and feedback connectivity across the cortical hierarchy. Methods: Eight subjects underwent left occipital TMS coupled with high-density EEG recordings during wakefulness and propofol-induced unconsciousness. Spectral analysis was a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 62 publications
(97 reference statements)
1
25
0
Order By: Relevance
“…For example, primary sensory cortex is still responsive to environmental stimuli, and basic organizational features such as frequency tuning in auditory cortex are preserved (Nir et al, 2015; Raz et al, 2014), while responses in higher order cortical sensory areas are largely suppressed (Liu et al, 2012; Wilf et al, 2016). In addition, cortical connectivity, which is central to leading theories of consciousness (Dehaene and Changeux, 2011; Friston, 2005; Tononi et al, 2016), is altered upon LOC during anesthesia (Boly et al, 2012a; Lee et al, 2017; Lee et al, 2013b; Murphy et al, 2011; Ranft et al, 2016; Sanders et al, 2018) and non-rapid eye movement (NREM) sleep (Boly et al, 2012b; Spoormaker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, primary sensory cortex is still responsive to environmental stimuli, and basic organizational features such as frequency tuning in auditory cortex are preserved (Nir et al, 2015; Raz et al, 2014), while responses in higher order cortical sensory areas are largely suppressed (Liu et al, 2012; Wilf et al, 2016). In addition, cortical connectivity, which is central to leading theories of consciousness (Dehaene and Changeux, 2011; Friston, 2005; Tononi et al, 2016), is altered upon LOC during anesthesia (Boly et al, 2012a; Lee et al, 2017; Lee et al, 2013b; Murphy et al, 2011; Ranft et al, 2016; Sanders et al, 2018) and non-rapid eye movement (NREM) sleep (Boly et al, 2012b; Spoormaker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying TC disengagement, there is a corresponding reduction in anterior-to-posterior symbolic transfer entropy (STE) and global permutation entropy (where entropy is a surrogate marker of information transfer) as measured by EEG ( Figure 2B), consistent with reduced information processing in the cortex [81]. The loss of connectivity along the anteriorposterior axis in response to an appropriate dose/concentration of a general anesthetic, along with the accompanying loss of information transfer along that axis, both feedforward and feedback -( [82] and references therein), is associated with loss of consciousness. Whether the loss of such connectivity is necessary and sufficient to produce unconsciousness is an open question, hopefully one that can be answered given limits on appropriate assays and definitions of consciousness itself.…”
Section: Anesthetic-induced Loss Of Consciousness In Humansmentioning
confidence: 60%
“…In his research at the University of Wisconsin, Rob confirmed that "connectedness" can indeed vary independently of consciousness and responsiveness, both under anesthesia and during sleep. 5 He also found that unresponsiveness is associated with changes in feed-forward cortical connectivity 6 -an intuitive contrast to the changes in feedback cortical connectivity that other investigators have associated with unconsciousness. This work adds substantially to our understanding of the brain, and how it can be impacted by drugs and disease.…”
mentioning
confidence: 94%